COMPARATIVE ANALYSIS ON THE PERFORMANCE PROPERTIES OF DIFFERENT TYPES OF PVC WINDOWS (Innovation in Woodworking Industry and Engineering design, 2026)
The behaviour of wooden, aluminium and various types of PVC joinery has been studied in extreme conditions with a testing device. The resistance of different types of joinery has been determined in occurrence of wind, air and water influence. The sound insulation and heat transfer properties of the double glazing windows made of different materials or a different design have been compared. Based on the studies conducted, the systems with the most stable performance have been established.